Intranasal glyphosate-based herbicide administration alters the redox balance and the cholinergic system in the mouse brain - Gallegos, Cristina Eugenia (2020)
Pesticide exposure is associated with cognitive and psychomotor disorders. Glyphosate-based herbicides (GlyBH) are among the most used agrochemicals, and inhalation of GlyBH sprays may arise from frequent aerial pulverizations. Previously, we described that intranasal (IN) administration of GlyBH in mice decreases locomotor activity, increases anxiety, and impairs recognition memory. Then, the aim of the present study was to investigate the mechanisms involved in GlyBH neurotoxicity after IN administration. Adult male CF-1 mice were exposed to GlyBH IN administration (equivalent to 50 mg/kg/day of Gly acid, 3 days a week, during 4 weeks). Total thiol content and the activity of the enzymes catalase, acetylcholinesterase and transaminases were evaluated in different brain areas. In addition, markers of the cholinergic and the nigrostriatal pathways, as well as of astrocytes were evaluated by fluorescence microscopy in coronal brain sections. The brain areas chosen for analysis were those seen to be affected in our previous study. GlyBH IN administration impaired the redox balance of the brain and modified the activities of enzymes involved in cholinergic and glutamatergic pathways. Moreover, GlyBH treatment decreased the number of cholinergic neurons in the medial septum as well as the expression of the α7-acetylcholine receptor in the hippocampus. Also, the number of astrocytes increased in the anterior olfactory nucleus of the exposed mice. Taken together, these disturbances may contribute to the neurobehavioural impairments reported previously by us after IN GlyBH administration in mice.